THE THE IMPACT OF FINANCIAL INCLUSION ON AGRICULTURAL DEVELOPMENT IN NGOKETUNJIA DIVISION, NORTH WEST CAMEROON: Financial Inclusion and Agriculture - Muafueshiangha, Ibrahim Menkeh (Global journal of Business and Integral Security, 2021)
Agriculture remains the backbone of many developing countries, with an increasing contribution to the gross domestic product. In Cameroon, more than 80% of the population is involved in agriculture, yet the sector is plagued by mounting challenges. With large expanses of very fertile land, Ngoketunjia Division would theoretically boast of food self-sufficiency and feed the rising population. On the contrary, these fertile lands co-exist with low agricultural productivity and yield. Therefore, this study investigates this dilemma and questions the role of financial inclusion in the productivity of agriculture in the Ngoketunjia Division. The main objective of this study, therefore, is to investigate the contribution of financial inclusion on the productivity of agriculture in Ngoketunjia Division, North West region of Cameroon. In other to attain this objective, data was collected from 285 farmers in Ngoketunijia using a structured questionnaire from a cross-section of the farming population. The data were treated and analyzed using structural equation modeling technique, and particularly the Partial Least Square Approach. Pre-tests conducted such as the convergent validity, average variance extracted (AVE), Cronbach's alpha, and convergent validity all indicated that the instrument was valid and reliable. The data set was further analyzed using the SmartPLS3.0 version. In this process, we have demonstrated that there is the absence of financial inclusion in the region as mainstream financial institutions are largely absent, hence limiting access to resources. This makes the contribution of financial inclusion to agricultural productivity in the region below par. The main hypothesis that financial inclusion has a statistically significant effect on agricultural productivity was as a consequence rejected which further justifies the fact that farmers are largely excluded from financial services in the region. We furthermore proved that education and training play a positive and significant role in the productivity of farmers in Ngoketunijia, irrespective of the variability of the weather condition. Post-tests conducted such as the Variance Inflation Factor (VIF) indicate no issue of multicollinearity and hence result validated with 99% confidence based on a probability value of 0.00, which implies that the overall conclusion is significant. It is recommended that measures should be put in place to ensure pragmatic education for farmers as well as ensure financial sector development for it to benefit the farming population. More youths should be encouraged and supported to adopt agriculture as a business, in line with the head of state’s vision on second-generation agriculture. It is concluded that agriculture remains the backbone of the economy and efforts to upgrade the performance of the sector should be intensified.